Lead and copper-induced hormetic effect and toxicity mechanisms in lettuce (Lactuca sativa L.) grown in a contaminated soil - Li, Jianhong; Qiu, Yong; Zhao, Qingjie; Chen, Dongliang; Wu, Zhipeng; Peng, An-An; Niazi, Nabeel Khan; Trakal, Lukáš; Sakrabani, Ruben; Gao, Bin; Wang, Hailong; Wu, Weidong (The Science of the total environment, 2020)
Lead (Pb) and copper (Cu) contamination seriously threatens agricultural production and food safety. This study aims to investigate Pb and Cu induced hormetic effect and toxicity mechanisms in lettuce (Lactuca sativa L.) and establish reliable empirical models of potentially toxic elements (PTEs) transfer in the soil-plant system. The content and distribution of Pb and Cu at subcellular levels in lettuce plants were examined using inductively coupled plasma-mass spectrometry, differential centrifugation and micro-X-ray fluorescence spectroscopy. The PTE-loaded capacity of Pb that ensures food safety was lower than that of Cu in the studied soil, but the PTE-loaded capacity of Pb that limits yield was higher than that of Cu. Lead in lettuce roots mainly accumulated in the cell wall (41%), while Cu mainly accumulated in the vacuoles (46%). The Pb and Cu were primarily distributed in the radicle of lettuce seeds under severe PTE stress, resulting in no seed development. Iron plaque formed on the root surface of lettuce seedlings and sequestered Pb and Cu via chelation. At the same concentration, lettuce was less tolerant to Cu in contaminated soil than Pb due to the higher activity of Cu ions in the soil. Lead was more phytotoxic to lettuce than Cu, however, since the radicle emerged from the seed under severe Cu levels, while it did not protrude under severe Pb levels. The potentially damaging effect of Pb in the visually healthy lettuce appeared to be higher than that of Cu under the same soil contamination level.
Keywords: olovo; salát (hlávkový); Lactuca; Soil Pollutants; Safe lettuce production; Soil contamination; μ-XRF; Metals, Heavy; Potentially toxic element; látky znečišťující půdu; měď; Soil; Copper; Lead; půda; těžké kovy; PTE-loaded capacity